Assessing the Adequacy of Aesthetic Nature and Maintenance of School Grounds of the Lagos State Public Schools: A Step Toward Sustainable Development - Olaide Alabi (Interdisciplinary Journal of Education, 2021)
The purpose of this study was to assess the quality of aesthetic nature of school grounds of Lagos state public schools: a step toward sustainable development. Two research questions were raised for the study. Multi-stage sample was used, where forty-six schools were purposively selected from two districts to participate in the study. A descriptive survey design was adopted, and checklist and questionnaire were used to collect data. The reliability coefficients of the instruments were found to be 0.85 and 0.84. The findings show that Lagos State Junior Secondary Schools did not regard the major relevance of the aesthetic nature of school grounds, such as good quality hedges; walkways, flower beds, ornamental trees, grassed fields, car parks and assembly grounds, therefore they do not have quality aesthetic designs for school grounds. On how schools were maintained with regards to floods during the rainy season, results show that the following categories of these agents participated in controlling flood: 22 (48%) schools enjoyed government intervention; 13 (28%) schools made use of students to control flood and 11 (24%) enjoyed no assistance from any quarters. None of the schools received parents’ intervention. It was therefore recommended that government should ensure that school grounds should be given special attention and should be designed to add befitting attraction to the school environment.